Thailand the worldly kingdom - Peleggi, Maurizio. (Reaktion Books, 2007)
Tourist adverts and glossy publications present Thailand as an exotic country with a rich cultural heritage, strong religious traditions and a much-loved monarchy. Historians too have contributed to Thailand's international allure by asserting its unique historical and cultural continuity in comparison to the other countries of South-east Asia, whose modern histories are stained by colonialism and nationalist struggles for independence.